The Book of Enoch and Early Astronomical Thought: A Prelude to Scientific Observation - Goshu, Belay Sitotaw (Budapest International Research and Critics University, 2025)
The astronomical content of 1 Enoch and its influence on ancient and early modern philosophy is examined in this study, with particular attention paid to cosmological concepts, celestial motions, and timekeeping systems. The primary objective is to analyze the Astronomical Book of 1 Enoch with other ancient cosmological texts, assess its role in shaping early Jewish and Christian timekeeping practices, and evaluate its influence on medieval and Renaissance scientific thought. A textual analysis was conducted to examine the structure and content of 1 Enoch, a comparative study was employed to compare its celestial descriptions with those of Mesopotamian and Egyptian systems, and a historical analysis traced its impact on later theological and scientific advances. The study finds that the 364-day solar calendar in 1 Enoch aligns more closely with the Mesopotamian and Egyptian traditions than with traditional Jewish lunar calendars. Additionally, 1 Enoch's cosmology influenced medieval and Renaissance thinkers, contributing to theological discussions on divine order and precision in the cosmos. The study concludes that 1 Enoch played a significant role in the progress of ancient and medieval astronomy, influencing theological debates and scientific advancements. It recommends further research into the integration of Enochian cosmology in early scientific thought and its potential role in shaping the progress of timekeeping systems.